Kurangnya Pemahaman Siswa Terhadap Materi Hidup Bermartabat Pada Dimensi Bernalar Kritis di SMKN 8 Semarang - Ayu Wiediyati Kusumasari (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
. School is a place for learning and good behavior, a real integral part of society, as well as a level and continuous educational unit for teaching and learning activities. Learning that is centered on appreciating life can shape students' character, teach ethics in social relationships, and help them recognize human values. Problem-based learning can help students live dignified lives and provide long-term benefits, creating citizens who are caring, responsible and contribute positively to society. The aim of the research is to increase students' understanding of the material on living with dignity in the critical reasoning dimension. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. The descriptive approach aims to analyze the description of the facts that occurred, so that by using a descriptive qualitative approach with the Problem Based Learning learning model, it will be seen about students' understanding of the material on living with dignity in the critical reasoning dimension of phase F at SMKN 8 Semarang.